2004
DOI: 10.1007/s00394-004-0477-z
|View full text |Cite
|
Sign up to set email alerts
|

Energy value of a low-digestible carbohydrate, NUTRIOSE� FB, and its impact on magnesium, calcium and zinc apparent absorption and retention in healthy young men

Abstract: NUTRIOSE FB can be used as a "bulking" agent, and substituted up to 50 g/d for usual maltodextrins without causing digestive disorders in healthy subjects. It would reduce intestinal transit disorders and energy intake, and improve magnesium and calcium absorption and retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 34 publications
7
63
2
Order By: Relevance
“…NUTRIOSE® is a purified resistant dextrin (Roquette Frères, Lestrem, France), a glucose polymer processed from wheat or corn starch heated at high temperature and adjusted to a low moisture level in the presence of an acid catalyst [13]. During a highly controlled process of dextrinization, the starch undergoes a degree of hydrolysis followed by repolymerization that converts it to fiber [14].…”
Section: Study Substancementioning
confidence: 99%
See 1 more Smart Citation
“…NUTRIOSE® is a purified resistant dextrin (Roquette Frères, Lestrem, France), a glucose polymer processed from wheat or corn starch heated at high temperature and adjusted to a low moisture level in the presence of an acid catalyst [13]. During a highly controlled process of dextrinization, the starch undergoes a degree of hydrolysis followed by repolymerization that converts it to fiber [14].…”
Section: Study Substancementioning
confidence: 99%
“…NUTRIOSE® is a purified resistant dextrin, a glucose polymer processed from wheat or corn starch and is considered as a dietary fiber [13][14][15]. In a first study, NUTRIOSE® supplementation for 12 weeks has demonstrated positive effects on body composition, energy intake and hunger in overweight men at a dosage of 34g/day [16].…”
Section: Introductionmentioning
confidence: 99%
“…Two trials reported on chemically modified resistant starch (RS 4 ) in relation to faecal wet weight, which was an insufficient number to enable a meta-analysis to be performed. Resistant starch supplementation appeared to have little effect on intestinal transit time (Tomlin & Read, 1990;Cummings et al, 1996;Silvester et al, 1997;Behall et al, 2002;Muir et al, 2004) or faecal moisture content (Cummings et al, 1996;Silvester et al, 1997;Heijnen et al, 1998;Vermorel et al, 2004). No further trials were identified in the update search (Colo-rectal health review p54-63).…”
Section: Faecal Weightmentioning
confidence: 99%
“…The doses range from 17-37g/day (mean 27g/d). Of the trials that investigate chemically modified resistant starch (RS 4 ) in relation to faecal wet weight, one reports 100g/day increases faecal weight (Vermorel et al, 2004), while the other observes no significant effect on faecal weight of 12g/day of three different corn and tapioca modified starches (Stewart et al, 2010).…”
mentioning
confidence: 99%
“…Only 15% is enzymatically digested in the small intestine, while the rest passes to the colon, where 75% of the initial amount is slowly and progressively fermented in the large intestine and 10% is excreted (Van den Heuvel et al, 2004). Nutriose would reduce intestinal transit disorders and energy intake, and improve magnesium and calcium absorption and retention (Vermorel et al, 2004). Its intake has been proved to prevent colonic inflammation and reduce intestinal transit disorders (Rozan et al, 2009;Pouillart et al, 2010), and its effects on total cecal weight, cecal content, cecal wall weight, pH, and short-chain fatty acid production could induce health benefits, since these effects are reported to be prebiotic .…”
Section: Introductionmentioning
confidence: 99%